Outer membrane protein profiles of Indian Isolate of Pasteurella multocida serotype B:2 - DEY, S; SINGH, V P (The Indian Journal of Animal Sciences, 2011)
Outer meInbrane proteins (OMPs) of 36 isolates of Pasteurella rnultocida serotype B:2 belonging to buffalo, cattle, pig, sheep and goat including a vaccine strain’ (P52) were isolated by the sarcosyl extraction Inethod. The size of OMP of P. Jnultocida serotype B:2 isolates and the’ ’vaccine strain ranged between 18 and 93 kDa in SDS-PAGE. Son1e variations were observed in few i?olates with respect to OmpA, OmpH and other minor proteins. Out of 36 isolates of P. lnultocida, 99.44% of isolates ’belonged to OMP type 1 (OmpA -37 kDa, OlnpH -32 kDa) while, 5.56% of isolates represented the OMP type 2 (OmpA ....37 kDa" OmpH -36.5 kDa). Comparison of P. rnultocida serotype B:2 OMP profiles from different species" showed little diversity. Â